Sukralfat as a Therapy for Reducing Itching and Repairing the Skin Barrier: A Systematic Review - Alia, Vrenda; Widhiati, Suci; Oktavriana, Triasari; Lidjaja, Lifesia Natali; Noviani, Laura (Newinera Publisher, 2024)
Sucralate is an aluminum salt from sucrose octasulfate that is known for its anti-ulcer activity, mucosal protection, and anti-mucositis potential. Recently, sucralfat has been used topically for the healing of various epithelial wounds, including ulcers, inflammatory dermatitis, mucositis, and burns. This systematic review aimed to evaluate the effectiveness of sucralfat as a topical therapy in reducing itching (pruritus) and improving the skin barrier. The analysis method used is Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA). A literature search was conducted on studies from 2004 to 2024 using keywords such as